The Contents af Fatty Acid, Cholestrol, and Description of Tissue in Fresh and Boiled Eel - Agoes Mardiono Jacoeb; Pipih Suptijah; Rezki Kamila (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Eel (Monopterus albus) is an aquatic biota that have a high nutrient content such as fatty acids and cholesterol. The purpose of this research was to determine the chemical composition, fatty acid, cholesterol, and description of tissue in fresh dan boiled eel. The research was carried out in several steps include sampling, sample preparation, morphometric and yield calculations, boiling eel for 20 minutes at 100ºC. Analysis performed in fresh and boiled eel was proximate analysis, fatty acids, cholesterol, and observation of tissue structure. The highest content of saturated fatty acids (SFA) in fresh eel was palmitic acid 13.79%, the highest content of monounsaturated fatty acid (MUFA) was oleic acid 19.45%, the highest content of polyunsaturated fatty acid (PUFA) was linoleic acid 7.42%. The content of fatty acid and cholesterol in eel has changed overall due to the boiling process. The content of cholesterol were 60 mg/100 g (in fresh eel) and 56.32 mg/100 g (in boiled sample). The structure of eel’s tissue changed due the boiling process.Keywords: cholesterol, eel (Monopterus albus), fatty acid, tissue structure